Dynamic capabilities in media management research: a literature review. Issue 2 (1st April 2020) - Murschetz, Paul Clemens; Omidi, Afshin; Oliver, John J.; Kamali Saraji, Mahyar; Javed, Sameera
Abstract : Purpose: Dynamic capabilities (DCs) help media firms adapt to rapidly changing environments. The purpose of this study is to provide a comprehensive literature review of studies of DCs in strategic management research with a view to understanding its implications for the management of media organizations. Essentially, it fertilizes on the idea that the concept of DC is useful and vital for answering various critical questions regarding the challenges that media organizations are currently facing. Design/methodology/approach: This study builds on a systematic literature reviewing design as the research methodology. It aims to identify, critically evaluate, and integrate factors, dimensions, and findings on studies of DCs in strategic management research and builds knowledge transfers to the field of strategic management research in the media industry. Findings: The study shows that the DC framework helps media firms effectively respond to changing environments. The conceptual DC framework has implications for media strategy practice. Results indicate a considerable growth in the number of papers published related to the DCs in media organizations from 2003 to 2018. Originality/value: The study qualifies the relevance and validity of the DC framework in strategic management research for the field of strategic media management. It explores a research agenda in this domain by precisely explaining the significant trends in the theory of DC to shape managerial strategies in the media industry.